The THE EFFECTIVENESS OF BASIRU DIGITAL MEDIA IN IMPROVING THE PROFESSIONAL COMPETENCY OF PRESCHOOL TEACHERS IN SOUTH JAKARTA - nila fitria; Yufiarti Yufiarti; Nurbiana Dhieni (International Conferences on Early Childhood Education Proceedings, 2024)
Teachers have four competence that is pedagogic competence , competence personality , competence social , and competence professional . According to Director General Regulation No. 2626 of 2023 on Competency Professional there are 3 indicators that is knowledge content learning and methods teach it , characteristics and ways Study participant education , and curriculum and methods use it . The teacher 's abilities become not quite enough the teacher answers to become a competent teacher . BASIRU digital media is one media that helps increase teacher skills in method teach specifically teach literacy read write . Research that uses method study descriptive qualitative . Data collection techniques used is do interview to kindergarten teachers in the South Jakarta area. Data analyzed with reduce data. Based on results study that BASIRU digital media is effective can improven competence professional teachers because In BASIRU there are learning videos related Skills teaching teachers in teach literacy read write , book pocket literacy read writing , and teacher self -assessment in teach literacy read write . So that content the can enrich method teach teacher. It is hoped that teachers can think creative in develop self in increase competence professional .